A study on the therapeutic effect of precise clipping of intracranial aneurysms assisted by CTA and 3D-slicer software - He, Chuan; Cao, Gang; Yang, Ying; Zhong, Qi; Lei, Yongsheng; Tan, Xingshi; Lin, Xiaohong; Chen, Yaokun; Sun, Wenxiao (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the application of Computed Tomography Angiography (CTA) combined with 3D-Slicer software reconstruction technology in the diagnosis and preoperative planning of intracranial aneurysms, and to explore its positive significance in improving surgical outcomes for patients.MethodsFrom January 2021 to December 2023, a total of 24 patients diagnosed with intracranial aneurysms (25 cases) underwent craniotomy clipping surgery. We utilized 3D-Slicer to render and fuse preoperative CTA image data, and to formulate individualized surgical plans, including approach, bone window, anticipated protection of the aneurysm-bearing artery and perforating arteries, and compared these with the actual surgical procedures. The actual intraoperative conditions were used as the diagnostic reference standard to compare and analyze the morphology of intracranial aneurysms, assessing the consistency between preoperative planning and actual operations. Additionally, intraoperative and postoperative complications and prognosis were analyzed.ResultsIt was confirmed that among the 25 intracranial aneurysms, the combination of CTA and 3D-Slicer could effectively detect and reconstruct these aneurysms; quantifying the extent of bone window grinding could reduce the need for multiple bone grinding after opening the dura mater; the consistency in determining the stenosis of the aneurysm-bearing artery intraoperatively, the difficulty of reconstructing and separating the aneurysm neck, and the condition of the perforating arteries near the aneurysm was good, with Kappa values of 0.865, 0.779, and 0.635, respectively. However, the consistency in predicting the rupture orientation of the aneurysm was poor, with a Kappa value of 0.186. All aneurysms in this group were completely clipped, and no new signs of bleeding were found in the head CT within 24 h after surgery, and no signs of aneurysm recurrence were observed in the head CTA within 7 days.ConclusionIn summary, combining 3D-Slicer technology with CTA can accurately assess intracranial aneurysms and provide key anatomical information required for craniotomy clipping surgery to formulate surgical plans, which has a positive significance in reducing surgical complications. These findings not only lay the foundation for further exploration of related issues but also provide clinical doctors with more scientifically effective guidance for diagnosis and surgical planning.